1995
DOI: 10.1677/joe.0.1460169
|View full text |Cite
|
Sign up to set email alerts
|

Follicular dynamics and secretion of inhibin and oestradiol-17β during the oestrous cycle of the hamster

Abstract: Plasma and ovarian levels of inhibin were determined by a radioimmunoassay (RIA) at 3-h intervals throughout the 4-day oestrous cycle of hamsters. Plasma concentrations of FSH, LH, progesterone, testosterone and oestradiol-17 beta were also determined by RIAs. In addition, hamsters were injected at various times with human chorionic gonadotrophin (hCG) to determine the follicular development. The changes in plasma concentrations of FSH after injection of antisera to oestradiol-17 beta (oestradiol-AS) and inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 1 publication
(1 reference statement)
9
40
1
1
Order By: Relevance
“…The present findings are comparable with those of Yamada et al [12]. If the E 2 concentrations represent the number of maturing follicles [20], we can expect this simple superovulation method to result in ovulation and embryo recovery that are equal to those obtained with commonly used method with the multiple administration of pFSH combined with eCG.…”
Section: Discussionsupporting
confidence: 91%
“…The present findings are comparable with those of Yamada et al [12]. If the E 2 concentrations represent the number of maturing follicles [20], we can expect this simple superovulation method to result in ovulation and embryo recovery that are equal to those obtained with commonly used method with the multiple administration of pFSH combined with eCG.…”
Section: Discussionsupporting
confidence: 91%
“…The inhibitory effects of exogenous progesterone on folliculogenesis are demonstrated in cyclic rats through the hypothalamic-pituitary axis, especially via lowering serum LH [34]. The present results concerning with FSH secretion compare favorably with the results of passive immunization against inhibin in other animals, such as rats [26], hamsters [16,17], cows [14], mares [24] and sheep [21,36], implying passive immunization against inhibin can induce superovulation in guinea pigs. Inhibin has the ability to suppress FSH secretion by directly inhibiting expression of the gene encoding the FSH β subunit in the pituitary gland [3,22].…”
Section: Discussionsupporting
confidence: 74%
“…Passive immunization against inhibin can increase the secretion of FSH in female guinea pigs [29] as well as in the other animals [14,16,17,21,26]. However, the mechanism that regulates the onset and completion of the compensatory response to hemiovariectomy remains obscure in guinea pigs.…”
mentioning
confidence: 99%
“…Because expression of -subunit mRNA in granulosa cells increased as follicles developed, the increase in ovarian -subunit mRNA levels during the follicular phase is probably due to development of large follicles to be selected for ovulation. However, previous studies indicated that in the golden hamster, the ovary of day 3 was most abundant in healthy large follicles, and the number of healthy large follicles decreased from day 3 to the morning of day 4 (Greenwald 1991, Kishi et al 1995. Therefore, -subunit mRNA levels do not reflect merely the number of large healthy follicles.…”
Section: Figurementioning
confidence: 89%
“…For example, the corpus luteum in the cyclic ovary always begins to show signs of histological regression by 3 days after ovulation and almost completely vanishes by the next ovulation (Grady & Greenwald 1968). In addition, the follicle-stimulating hormone (FSH) surge during the periovulatory period is clearly separated into two peaks in the golden hamster (Bast & Greenwald 1974, Kishi et al 1995 unlike the rat in which the FSH surges almost overlap (Watanabe et al 1990).…”
Section: Introductionmentioning
confidence: 99%